2007
DOI: 10.1136/emj.2006.042671
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department follow-up of bereaved relatives: an audit of one particular service

Abstract: It is suggested that the provision of information is theoretically beneficial to the bereavement process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Our findings fit with those of Parris et al 4 who described a consultant-led bereavement service for families of patients who died in the emergency department. They had a similar finding of 14% of families taking up the offer of a meeting 4. In this study, they waited 4–6 weeks before sending out the invitation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings fit with those of Parris et al 4 who described a consultant-led bereavement service for families of patients who died in the emergency department. They had a similar finding of 14% of families taking up the offer of a meeting 4. In this study, they waited 4–6 weeks before sending out the invitation.…”
Section: Resultssupporting
confidence: 91%
“…The ability to understand how the loss has occurred appears to reduce the risk of a prolonged and abnormal grief reaction in the bereaved. Families who seek support from hospital bereavement services do so because of clinical questions over the diagnosis, investigations, treatment and ‘what if’ scenarios, questions over the death certificate or postmortem, or because of quality of care issues such as issues around communication 4 5…”
Section: Introductionmentioning
confidence: 99%
“…An ED that routinely writes to relatives offering a meeting with a Consultant to discuss factual issues concerning the death audited their service in 2007 (Parris et al, 2007). They found that 14% of bereaved relatives replied to take up the offer and 27% replied declining the offer (the 14% acceptance rate is similar to the 11% acceptance rate found by the Australian study discussed above).…”
Section: Follow-up For the Bereavedmentioning
confidence: 99%
“…16 Eleven articles surveyed families, friends, or survivors of an accident that killed the patient. 2,3,[25][26][27][28][29][30][31][32][33] Six articles surveyed health professionals on death notification practices. 22,[34][35][36][37][38] There was one chart audit, 39 and there were 29 review articles describing notification in the emergency department and hospital.…”
Section: Measurement and Resultsmentioning
confidence: 99%